Genetic ablation of carbonic anhydrase IX disrupts gastric barrier function via claudin‐18 downregulation and acid backflux. (19th October 2017) - Li, T.; Liu, X.; Riederer, B.; Nikolovska, K.; Singh, A. K.; Mäkelä, K. A.; Seidler, A.; Liu, Y.; Gros, G.; Bartels, H.; Herzig, K. H.; Seidler, U.
Abstract: Aim: This study aimed to explore the molecular mechanisms for the parietal cell loss and fundic hyperplasia observed in gastric mucosa of mice lacking the carbonic anhydrase 9 (CAIX). Methods: We assessed the ability of CAIX‐knockout and WT gastric surface epithelial cells to withstand a luminal acid load by measuring the pHi of exteriorized gastric mucosa in vivo using two‐photon confocal laser scanning microscopy. Cytokines and claudin‐18A2 expression was analysed by RT‐PCR. Results: CAIX‐knockout gastric surface epithelial cells showed significantly faster pHi decline after luminal acid load compared to WT. Increased gastric mucosal IL‐1 β and iNOS, but decreased claudin‐18A2 expression (which confer acid resistance) was observed shortly after weaning, prior to the loss of parietal and chief cells. At birth, neither inflammatory cytokines nor claudin‐18 expression were altered between CAIX and WT gastric mucosa. The gradual loss of acid secretory capacity was paralleled by an increase in serum gastrin, IL‐11 and foveolar hyperplasia. Mild chronic proton pump inhibition from the time of weaning did not prevent the claudin‐18 decrease nor the increase in inflammatory markers at 1 month of age, except for IL‐1 β . However, the treatment reduced the parietal cell loss in CAIX‐KO mice in the subsequent months. Conclusions: We propose that CAIX converts protons that either backflux or are extruded from the cells rapidly to CO2 and H2 O, contributing to tight junction protection and gastric epithelial pHi regulation. Lack of CAIX results in persistent acid backflux via claudin‐18 downregulation, causing loss of parietal cells, hypergastrinaemia and foveolar hyperplasia.